Creating Information System and Knowledge Base Supporting Environmental Modelling in the Hungarian North-Great Piain Region - Lénárt, Csaba (Acta Agraria Kaposváriensis, 2002)
The need for better tools to handle ever more critical environmental and resource management problems is obvious, and the rapidly developing field of information technology can provide the necessary machinery. The integration of models and geographic information systems, expert systems, and interactive graphics, generating a virtual reality version of the decision problem, is a promising and challenging development in environmental systems analysis, strategic decision support, and applied informatics. The biggest challenge, however, seems to be the integration of new information technologies and more or less mature formal methods of analysis into the environmental engineering education, that is, putting these tools to work in practice. Geographic Information Systems (GIS) have become indispensable tools for watershed scale hydrologie analysis and modeling. The integrative capabilities of GIS can emulate real-world complexity, facilitating interdisciplinary research and communication. The management of natural resources requires the integration of often very large volumes of disparate information from numerous sources; the coupling of this information with efficient tools for assessment and evaluation that allow broad, interactive participation in the planning, assessment, and decision making process; and effective methods of communicating results and findings to a broad audience. Our goal was to create a regional DGPS network, data warehouse and method in this field due to the importance of the location-based decision support, because it is essential to protect the environmental resources in the North-Great-Plain Region, as it is one of the most important environmental resources in Hungary.